Pengaruh Komposisi Subtrat dari Campuran Kotoran Sapi dan Rumput Gajah (Pennisetum purpureum) terhadap Produktivitas Biogas pada Digester Semi Kontinu - Agus Haryanto; Rivan Okfrianas; Winda Rahmawati (Jurnal Rekayasa Proses, 2019)
A B S T R A C TThis study aims to determine the effect of substrate composition on biogas production from a mixture of cow dung and elephant grass using semi-continuous digester. Fresh cow dung and elephant grass were obtained from Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. Elephant grass was knife-chopped, crushed using a blender and then mixed with cow dung at a total solid (TS) ratio between elephant grass and cow dung varies from 35:65 (P1), 40:60 (P2), 45:55 (P3), and 50:50 (P4). This mixture was then diluted with tap water until its TS content reach 5% and was used as substrate. Four semi-continuous digesters (labeled as P1 to P4) having a capacity of 36 L and working volume of 28 L were initially loaded with 22 L of diluted fresh cow dung (dilution ratio of 1:1) as a starter (source of bacteria) and were left until stable condition. When the biogas was produced, the prepared substrate was added daily into the respective digester at a loading rate of 500 mL.d-1. Parameters to be observed included daily temperature and pH of the substrate, daily biogas production, TS and VS content, and biogas quality. The results showed that the digester worked at average pH of 6.9 and the daily temperature 26.3 to 29.7°C. The total biogas production for 60 days was 608.4, 676.8, 600.0, and 613.3 L, respectively for P1, P2, P3, and P4. Biogas yield after the substrate achieving the designed composition was 254 (P1), 260 (P2), 261 (P3), and 271 L.m-3 of the substrate (P4). The addition of elephant grass up to 50% could maintain high production of biogas.Keywords: biogas; cow dung; elephant grass; productivity; semi-continuous A B S T R A KPenelitian ini bertujuan untuk mengetahui pengaruh komposisi substrat terhadap produktivitas biogas dari campuran kotoran sapi dan rumput gajah pada digester semi kontinu. Rumput gajah dan kotoran sapi segar diperoleh dari Jurusan Peternakan, Fakultas Pertanian, Universitas Lampung. Rumput gajah dipotong menggunakan pisau dan dihancurkan dengan blender hingga halus dan dicampurkan dengan kotoran sapi pada perbandingan berat padatan kering (TS) 35:65 (P1), 40:60 (P2), 45:55 (P3), dan 50:50 (P4). Campuran ini diencerkan dengan air hingga kandungan TS mencapai 5% dan digunakan sebagai substrat. Empat digester semi kontinu (diberi label P1 hingga P4) dengan volume kerja 28 L mula-mula diisi dengan 22 L starter kotoran sapi segar yang diencerkan dengan air pada perbandingan berat 1:1 dan dibiarkan hingga stabil. Setelah gas mulai diproduksi, substrat yang telah dipersiapkan (sesuai label) ditambahkan ke dalam masing-masing digester dengan laju pembebanan 500 mL hari-1. Parameter yang diamati meliputi suhu harian, pH substrat, kandungan TS dan VS, produksi biogas, dan kualitas biogas. Hasil penelitian menunjukkan bahwa digester bekerja pada pH rata-rata 6,9 dan suhu harian antara 26,3–29,7°C. Total produksi biogas selama 60 hari adalah 608,4; 676,8; 600,0; dan 613,3 L berturut-turut untuk P1, P2, P3, dan P4. Produktivitas biogas setelah substrat mencapai komposisi yang direncanakan adalah 254 (P1), 260 (P2), 261 (P3), dan 271 L/m-3 substrat (P4). Penambahan rumput gajah hingga 50% masih menghasilkan biogas yang tinggi.Kata kunci: biogas; kotoran sapi; produktivitas; rumput gajah; semi-kontinu